2013
DOI: 10.1002/jso.23347
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open radical hysterectomy in patients with stage IB2 and IIA2 cervical cancer

Abstract: LRH has similar therapeutic efficacy to ORH in patients with bulky early-stage cervical cancer. However, LRH has more favorable surgical outcomes. Therefore, LRH is not only a reasonable alternative to ORH but also the preferred surgical procedure for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 32 publications
3
46
0
Order By: Relevance
“…Worldwide, several cancer centers have undergone a paradigm shift towards increasing the use of minimally invasive surgical techniques, especially robotic‐assisted laparoscopy (e.g. for localized endometrial and cervical cancer), and several studies have confirmed their safety in terms of adverse events and oncologic outcomes . Consequently, it is likely that future studies will focus on further decreasing the duration of hospital stay for patients undergoing more advanced surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, several cancer centers have undergone a paradigm shift towards increasing the use of minimally invasive surgical techniques, especially robotic‐assisted laparoscopy (e.g. for localized endometrial and cervical cancer), and several studies have confirmed their safety in terms of adverse events and oncologic outcomes . Consequently, it is likely that future studies will focus on further decreasing the duration of hospital stay for patients undergoing more advanced surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In the present review, having a malignant indication for mini- and several studies have confirmed their safety in terms of adverse events and oncologic outcomes. [38][39][40][41][42] Consequently, it is likely that future studies will focus on further decreasing the duration of hospital stay for patients undergoing more advanced surgical procedures.…”
Section: Charlson Comorbidity Index <5mentioning
confidence: 99%
“…Table 2 summarizes the findings of various studies comparing the laparoscopic approach versus the conventional open access [25,26,27,28,29,30,31]. Other studies have concluded that the laparoscopic, or laparoscopic-assisted vaginal radical hysterectomy results in less overall morbidity, less blood loss, fewer transfusions, a shorter hospitalization (by 3 days), a longer surgical time, and equal recurrence rates as compared to the classical open management [32,33,34,35,36].…”
Section: Laparoscopic Versus Open Surgical Accessmentioning
confidence: 99%
“…Park retrospectively compared the survival and surgical outcomes of 115 laparoscopic radical hysterectomy (LRH) vs 118 open radical hysterectomy (ORH) in patients with stage IB2 to IIA2 [ 12 ]. Conversion to laparotomy occurred in two patients.…”
Section: Radical Hysterectomy and Nervesparing Surgerymentioning
confidence: 99%